(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: To determine the rate, distribHAIson, agents and some related factors of hospital-acquiered infection in patients with COVID-19. Method: A cross-sectional study was conducted on 254 COVID-19 patients. Results: Among 254 patients who were eligible for the research, the rate of hospital-acquiered infection was 7.1%. In which, lung infections accounted for the highest rate (78.3%), followed by sepsis (13.1%), surgical site infections (4.3%), and other infections (4.3%). The most of causative agent is K.pneumoniae (29.6%), followed by A.baumannii (14.8%). In the logistic regression analysis, risk factors of HAIs in COVID-19 patients were blood disease (OR = 1.1; p < 0.05), intensive care (OR = 972.6; p < 0 ,05) and central venous catheter (OR = 19.1; p < 0.05). There was a statistically significant difference (p <0,01) in mortality in the group of patients with HAIs and the group of patients with no HAIS, whereby the group of patients with HAIS (77,8%) had a higher mortality rate than the group of patients without HAIS (1,3%) (OR = 271,8; KTC 95: 554 - 13345). Conclusion: Lung infection is the most common hospital-acquiered infection in patients with COVID-19. Most of the pathogens that cause hospital-acquired infections are multi-antibiotic resistant Gram (-) bacteria such as K.pneumoniae and A.baumannii. Mortality was the highest in patients with nosocomial pneumonia. Further studies are needed to research the risk factors and prevention of nosocomial pneumonia in patients with COVID-19.